Local Technical Agroclimatic Committees (LTACs) approach generating climate forecasts and crop response - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Currently, LTAC approach developed by CCAFS is being implemented in 5 countries in Latin America reaching 23 LTACs (Colombia (9), Honduras (10), Guatemala (1), Nicaragua (2) and Chile (1)) by different stakeholders including national and local governments, producers associations, civil society among others.